Effects of dry-land strength training on swimming performance outcomes in competitive swimmers: a systematic literature review - Naluri Denay; Pringgo Mardesia (JRTI (Jurnal Riset Tindakan Indonesia), 2025)
Dry-land strength training is now embedded in the weekly programming of competitive swimmers, yet the specific modalities, loading strategies and dosages that produce the most consistent transfer to swimming performance remain contested. This systematic literature review aimed to (i) map the dry-land strength training interventions applied to competitive swimmers; (ii) characterise their effects on swimming performance outcomes; and (iii) identify the programme characteristics associated with the greatest performance gains. The review was reported in line with the PRISMA 2020 statement. Scopus was searched with a purpose-built Boolean string, limited to English-language original journal articles published between 2021 and 2025 and available as open access, yielding 216 initial records. After removing 15 duplicates, 201 records were screened by title and abstract, 58 reports were sought for retrieval, and 54 full-text reports were assessed against pre-specified PICOS-based eligibility criteria. Twenty studies met all criteria and were retained for qualitative synthesis. Three convergent findings emerged: maximal and heavy-resistance strength training produced the most reproducible gains in sprint and start performance; concurrent dry-land plus in-water training generally outperformed either modality alone for stroke-specific outcomes; and horizontally directed and power-oriented dry-land work showed the strongest transfer to swim start metrics. The review contributes an evidence-informed framework for prescribing dry-land strength work in competitive swimming and highlights the need for larger, longer, standardised trials.